Private Participation in the Electricity Sector : Recent Trends - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Private participation in electricity industries has grown substantially since 1990, with electricity becoming one of the leading infrastructure sectors in attracting private investment. Between 1990 and 1997 the private sector took on the management, operations, rehabilitation, or construction risk of 534 electricity projects, with total investments of US$131 billion. These projects have been implemented under schemes ranging from management contracts with or without investment commitments to divestitures to greenfield facilities under build-operate-transfer (BOT), or similar arrangements. This Note provides an overview of the patterns and trends in these projects.